2006
DOI: 10.1246/cl.2007.60
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dipolar Cycloaddition of Ethyl Diazoacetate to Alkynes in the Pores of Zeolite NaY

Abstract: Zeolite NaY promotes 1,3-dipolar cycloaddition of ethyl diazoacetate to alkynes having an electron-withdrawing group to afford the corresponding functionalized pyrazoles in high yields. The activation of the dipolarophile inside the pores of NaY is proposed based on the 13C MAS NMR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…37 involve either highly reactive diazoalkanes generated in situ, 41,42 or highly stabilized diazo compounds 43 requiring elevated reaction temperatures 44 or toxic metal catalysts to attain useful reaction rates. [45][46][47][48][49][50] Now that a wide variety of diazo compounds are readily accessible from azides in a single step, we sought to assess their reactivity in strain-promoted cycloaddition reactions with forefront cycloalkynes.…”
Section: Introductionmentioning
confidence: 99%
“…37 involve either highly reactive diazoalkanes generated in situ, 41,42 or highly stabilized diazo compounds 43 requiring elevated reaction temperatures 44 or toxic metal catalysts to attain useful reaction rates. [45][46][47][48][49][50] Now that a wide variety of diazo compounds are readily accessible from azides in a single step, we sought to assess their reactivity in strain-promoted cycloaddition reactions with forefront cycloalkynes.…”
Section: Introductionmentioning
confidence: 99%
“…γ-Pyranone ring is often constructed by the intermolecular Michael addition of an enolate oxygen anion with conjugate ynones (an annulation reaction), as documented in the literature . Additionally, the [3 + 2] cycloaddition of diazo compounds with carbon–carbon triple bonds has been widely applied to construct pyrazole rings; however, the corresponding electrocyclizations toward these heterocycles are rarely utilized . The combination of the electrocyclization toward pyrazole synthesis and the annulation for γ-pyranone synthesis is not only interesting but also challenging.…”
mentioning
confidence: 99%
“…13 In 2004, Li realised a breakthrough by reporting the first intermolecular cycloaddition of various adiazocarbonyl molecules to electron-poor alkynes catalysed by indium(III) chloride in water. 14 More recently, Ready extended the scope of the reaction to a wide range of alkynes by using copper acetylides in THF, 15 while other developments involved zeolite NaY as promoter in CH 2 Cl 2 , 16 and microwave-assisted reaction with the alkyne as solvent. 17 During our research, we now found that the 1,3-dipolar cycloaddition of diazo compounds to alkynes did not need any special promoter or medium, and could be simply conducted under thermal conditions with various partners.…”
mentioning
confidence: 99%